Altered dynamics of mitochondria and reactive oxygen species in the erythrocytes of migrating red-headed buntings - Bhardwaj, Nitin; Kumar, Anit; Gupta, Neelu Jain (Frontiers in Physiology, 2023)
Background: Blood antioxidants provide propensity to mitigate Reactive Oxygen Species (ROS) apart from other oxidative challenges during high energy state of migration in night migratory songbirds. The study investigated the modulation of erythrocytes, mitochondrial abundance, haematocrit changes, and relative expression of fat transport-related genes during migration in redheaded buntings (Emberiza bruniceps). We hypothesized an increase in antioxidants along with the mitigation of mitochondria related ROS elevation and consequential apoptosis occurring during migration. Methods: Male redheaded buntings (n=6) were held under short days (8h of light and 16h of dark, 8L: 16D)/long days (14L: 10D), and photoinduced to simulated non-migratory nMig, pre-migratory pMig and migratory Mig states. Erythrocyte shape, ROS production, mitochondrial membrane potential (MMP), reticulocyte proportion and apoptosis were analysed using flow cytometry and relative expression of fat metabolising and antioxidant genes was measured by qPCR. Results: There was a significant increase in haematocrit and erythrocyte area. ROS, MMP and apoptotic erythrocyte proportion declined in Mig state. The changes in antioxidant genes (SOD1 and NOS2), fatty acid translocase (CD36), and metabolic (FABP3, DGAT2, GOT2 and ATGL) genes show a significant increment during Mig state. Conclusions: These results suggest adaptive changes occur in mitochondrial behaviour as well as apoptosis of erythrocytes. The transition in erythrocytes, antioxidant genes and fatty acid metabolism gene expressions suggest differences in regulatory strategies at the cellular/ transcriptional level during different states of migration in birds.